FLAIRS-36 Invited Talk Abstracts - Soon Chun (Proceedings of the International Florida Artificial Intelligence Research Society Conference)
Three invited speakers for the general conference include  Deborah L. McGuinness, Christoph Benzmüller and Bonnie J. Dorr.  The special track invite speaker is for Nobal Niraula for the Applied Natural Language Processing track.